Gender Fiqh: Mobilization of Gender-Responsive Movement on Social Media - Siti Nurjanah; Iffatin Nur (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2022)
This study aimed to reformulate the ijtihad of gender-responsive fiqh. Such ijtihad model is needed in order to respond to the developments and dynamics of life in the current contemporary era. Moreover, current social reality and condition are often associated with empowerment of and justice for women. Movements and responses toward women’s issues recently has been occurring quite monumentally on social media. Such movements represent a response toward media development, especially on social media platforms. This literature-based study collected data from literature studies and descriptive critical analysis. Through the critical analysis, this study found an interpretation of gender fiqh ijtihad model initiated through social media platforms.